Peningkatan Keterampilan Menulis Teks Deskripsi dengan Memanfaatkan Media Video pada Siswa Kelas VII-1 SMP Negeri 1 Alasa - Maru’ao, Eber Felora; Halawa, Sunida; Lahagu, Yarni Kristiani; Zebua, Fentri; Waruwu, Lestari (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The purpose of this study was to assess the impact of using video media in improving the writing skills of description text in class VII-1 students at SMP Negeri 1 Alasa. The learning method involving video media was applied during the research period, focusing on vocabulary development sentence structure, conformity of content to the title and understanding of context. This study used Classroom Action Research Design (PTK), the type of data collection used was descriptive qualitative and quantitative. The population of this study was all students in SMP Negeri 1 Alasa, while the subjects used in this study were students of class VII-1 as many as 28 people. The results showed a significant improvement in the quality of students' writing, indicating that the utilization of video media proved effective in improving the ability to write descriptive texts at that grade level.